Draft standard to match to and work with ETS 300 001/NET4 "Apparatus using cordless attachments (excluding cellular radio apparatus) for connection to analogue interfaces of public switched telephone networks run by certain public telecommunications operators". Specification for cordless telephone apparatus using radio links Part 2, (31st October 1992) - British Standards Institution,
No abstract available